Religious Integrity and Local Culture (Descriptive Study on Cicarucub Indigenous Peoples of Lebak Banten) - Dendi, Dede (Universitas Syiah Kuala, 2023)
The relationship between religion (Islam) and culture is often manifested in accommodative, complementary, and conflicting forms, but for the people of South Banten, the relationship between religion and culture (tradition) looks more complementary. Islam and ancestral culture have similar values, so a dynamic, dialectical relationship is created so that an integral relationship is realized. This study employs an ethnographic approach, which explains in depth about humans, in this case the Cicarucub community. The method used is a qualitative method; this method develops and solves problems that have been described and analysed in terms of religious and cultural integrity. The results of this study state that there are cultural meanings that have similarities with Islamic teachings. The relationship between religion (Islam) and culture (Sunda) is proof that Islam is a dynamic religion; it is permissible to modify new teachings as long as they do not conflict with the al-Qur`an, hadith, the consensus of the scholars (ijma'), and qiyas (analogy). Sundanese culture is also a very dynamic culture, able to coexist with religious teachings, especially Islam.